"Comparative Study of Conventional X-Ray, Digital Imaging and CBCT in the Detection of Approximal Caries in Primary Teeth (In Vivo Study)’’ (Journal of Hama University, 2020)
The aim of this study: Compare the accuracy of conventional and digital radiography and CBCT in the detecting of approximal caries in primary teeth in-Vivo, assess the accuracy of each of the radiological methods in determining the depth of proximal carious lesion. Considering direct clinical measurement of the proximal lesion extension is the golden standard.Materials and methods: The study samples consist of (30) primary teeth affected with proximal carious lesion. The sample was divided into three groups according to the radiographic techniques. Samples were undergoing visual examination in addition to visual inspection with dental probe to assess the presence of proximal lesion enable to detect by clinical examination. After taking radiographic images of the samples according to their radiographic groups, subsequent clinical curettage of the whole proximal carious lesion is done and the resulting depth is measured using a Vernier Caliper.The study included six different tests: visual examination, visual inspection with probe, conventional radiographic examination, digital radiographic examination, CBCT radiographic examination and direct clinical measurements with Vernier Caliper.Results: The study concluded superiority of conventional radiography over both digital imaging and CBCT imaging in detecting proximal carious lesion depth. Also, the three radiographic methods were effective in the diagnosis of proximal caries.Conclusions: The importance of using conventional radiography for the diagnosis and detection of proximal caries depth on child's primary teeth, as it provides us with accurate diagnostic information that affect in the treatment decision. Also, the use of radiographic diagnosis regardless of its type considered of importance in detecting proximal carious lesions, while we do not recommend the use of CBCT in children's in order to detect proximal caries only.
Keywords: Conventional Radiography, Digital Radiography, CBCT, Proximal Caries, Vernier Caliper.